Electron work function in individual multiwalled carbon nanotubes doped with nitrogen and boron - N. A. Davletkildeev; D. V. Sokolov; E. Yu. Mosur; I. A. Lobov (Омский научный вестник)
Multi-walled undoped and doped with nitrogen and boron carbon nanotubes have been synthesized by chemical vapor deposition. Based on the analysis of images obtained by electrostatic force microscopy at various tip voltage, the value of the external contact potential difference between the tip and individual carbon nanotubes is determined. Using the obtained value of the contact potential difference, the electron work functions for undoped and doped with nitrogen and boron individual carbon nanotubes are calculated, which amounted to 4,7; 4,6 end 5,75 eV, respectively.